Aproximación al estado actual del conocimiento de la avifauna del departamento del Atlántico, Colombia (2016)
In order to establish the current state of knowledge of the avifauna in Atlántico state (Colombia) a literature review and bibliography on ornithological studies, inventories of wildlife, field data available from various sources of information (libraries, databases, computer tools) was made, results indicate that the state currently has a total of 359 bird species, including 40 recent new records of avifauna. This represents 51% of the amount of bird species in the Caribbean region and 19% of all registered species in Colombia (N = 1903). Of the state’s total, eighty (80) are migratory, which represent 43% of the total of migratory birds in Colombia (N = 185). Also, in the Atlántico state territory there are two of the species listed in the Red Book of Colombia’s birds Phoenicopterus ruber and Chauna chavaria, representing only 1.23 % of a total of 162 species consider threatened or near threatened. In addition, five near-endemic species (Chauna chavaria, Chlorostilbon gibsoni, Picumnus cinnamomeus, Inezia tenuirostris and Synallaxis candei) inhabit the state.